1977
DOI: 10.1080/03610737708257085
|View full text |Cite
|
Sign up to set email alerts
|

Imagery in the aged

Abstract: Two studies were conducted to investigate the use of imagery by subjects of different ages. Experiment 1 was designed to test the effectiveness of "peg-word" system as a memory aid for the elderly. Variables believed to be important in the effectiveness of mnemonic devices were manipulated. The results showed that the mnemonic and imagery instructions were of benefit to the young subjects but not to the older subjects. Age was also found to interact with the concreteness variable, item concreteness having a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
3

Year Published

1980
1980
2002
2002

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 15 publications
4
28
0
3
Order By: Relevance
“…Finally, it is possible that the widening gap in recall found after training in the mne monic might be due to age differences in the ability to generate and retrieve visual images [Winograd and Simon, 1980], This explana tion was invoked by Mason and Smith [1977] in explaining their finding that young sub jects improved their recall through use of the peg-word mnemonic, whereas middle-aged and elderly subjects did not. Other research with this mnemonic [Poon et al, 1980.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that the widening gap in recall found after training in the mne monic might be due to age differences in the ability to generate and retrieve visual images [Winograd and Simon, 1980], This explana tion was invoked by Mason and Smith [1977] in explaining their finding that young sub jects improved their recall through use of the peg-word mnemonic, whereas middle-aged and elderly subjects did not. Other research with this mnemonic [Poon et al, 1980.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown older adults, given simple instructions to use a speci®c strategy, improved their subsequent performance on a memory task compared to other older adult groups not informed on the use of a particular strategy (Hertzog, McGuire, & Lineweaver, 1998;Mason & Smith, 1977;Treat & Reese, 1976).…”
mentioning
confidence: 99%
“…To encourage participants to focus on the items and their appearance, they were asked to rate how long it would take to draw the picture they were looking at or imagining (see Durso & Johnson, 1980). They were explicitly directed to generate images on the appropriate trials because evidence suggests that older adults do not necessarily spontaneously use imagery Mason & Smith, 1977) but can perform as well as younger adults on a variety of memory tasks when instructed to use imagery (e.g., Fullerton, 1983;Treat & Reese, 1976;Whitboume & Slevin, 1978;Wood & Pratt, 1987;Yesavage, Rose, & Bower, 1983). Later participants were given a surprise source test in which they indicated whether each item had been seen, imagined, or was new.…”
Section: The Source Monitoring Framework and Agingmentioning
confidence: 99%